ANALISIS FAKTOR KESULITAN BELAJAR SISWA PADA PEMBELAJARAN IPAS MATERI ORGAN PERNAPASAN MANUSIA KELAS V SD NEGERI 106815 MARINDAL TAHUN PEMBELAJARAN 2024-2025 - Haliza, Nurul; Fitrah Dwi, Dara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the factors of students' learning difficulties in learning Natural and Social Sciences (IPAS) on the material of human respiratory organs in class V of SD Negeri 106815 Marindal in the 2024-2025 academic year. Learning difficulties experienced by students can be caused by internal factors, such as health conditions, cognitive abilities, and motivation, as well as external factors, including teaching methods and environmental support. The methodology used in this study is a descriptive qualitative approach, with data collection through interviews, observations, and documentation. The research participants consisted of 28 students, 1 teacher, and 5 parents of students. The results showed that most students had difficulty understanding the scientific terms and concepts taught, which resulted in low learning outcomes. Monotonous teaching methods and the lack of use of interesting learning media also contributed to low student motivation and interest in learning. In addition, support from parents and a non-conducive learning environment also worsened this condition. This study recommends the need for improvements in teaching methods and increased support from parents to create a more effective learning environment, so that students can understand the material better and improve their academic achievement.